Experiential learning and mentorship as the foundation of clinical epidemiology training during infectious diseases fellowship: Response to "Training infectious diseases fellows for a new era of hospital epidemiology". Issue 1 (11th April 2022) - Day, Shandra R.; Sobhanie, Mohammad Mahdee; Colburn, Nora E.; Liscynesky, Christina
Abstract: A specific, clinical-epidemiology, month-long rotation for all infectious disease fellows as well as a 1-year subspecialty track provides education in clinical epidemiology during infectious disease fellowship training. We describe the educational process created at our institution to provide this training.